Spatial analysis of accretion, abrasion and shoreline change in banda aceh costal area. Issue 1 (February 2021) - Irham, M; Suri, R; Setiawan, I; Fuadi, A
Abstract: The coast of Banda Aceh City has a gentle sloping beach morphology, making it prone to changes in coastlines due to hydro-oceanographic dynamics. Areas that are particularly vulnerable are the mangrove areas and around the Krueng Aceh estuary and coastal area of Lampulo. Therefore, to determine the extent of shoreline changes, a spatial analysis of coastal vulnerability was carried out with the aim of knowing how much change had occurred at Lampulo beach in Banda Aceh City of Aceh Province. The research was conducted using Google Earth data technology and the use of Geographic Information System (GIS) software. The analysis was carried out over a period of 14 years starting from 2004 to 2017. Field data verification and georeferencing were also carried out to check the accuracy of mapping and calculations. The results showed that in 2004-2005 there was a large erosion that changed the shape of the coastal profile where the mangrove coastline turned into water without mangroves as a result of the tsunami on December 26, 2004. In 2008-2009, after the construction of the breakwater and the Port of Lampulo there was a large accretion occurred having the impact on the morphology of the coast. The results also concluded that the annual average accretion value was 20.48 ha and the annual abrasion was 19.28 ha. The value of shoreline reduction due to abrasion is around 217.25 ha and accretion of 166.56 ha over a period of 14 years.